2020
DOI: 10.13181/mji.oa.203787
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of advanced stage non-small-cell lung cancer patients receiving chemotherapy: adenocarcinoma <em>versus</em> squamous cell carcinoma

Abstract: BACKGROUND In Indonesia, lung cancer is one of the most prevalent solid cancer with the highest mortality rate. However, studies to identify prognostic factors associated with mortality are lacking. Thus, this study was aimed to determine the association of histological subtypes and prognosis of advanced stage non-small-cell lung cancer (NSCLC) patients receiving chemotherapy. METHODS This study focused on a retrospective cohort consisting of 60 patients with advanced stage NSCLC and treated with chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…4 Some studies in Indonesian oncology referral hospitals showed that over 90% of patients present with advanced stage of lung cancer. 9,10 Lung cancer prognosis is massively dependent on the disease stage. Hence, screening for lung cancer is needed as an effort to increase the survival rate.…”
Section: Screeningmentioning
confidence: 99%
“…4 Some studies in Indonesian oncology referral hospitals showed that over 90% of patients present with advanced stage of lung cancer. 9,10 Lung cancer prognosis is massively dependent on the disease stage. Hence, screening for lung cancer is needed as an effort to increase the survival rate.…”
Section: Screeningmentioning
confidence: 99%
“…1 Most lung cancer cases can only be diagnosed in advanced stages, resulting in high mortality rates. 2,3 The most common type of tumor in pulmonary cancer is squamous cell carcinoma (SCC). SCC mainly affects men and is more strongly associated with smoking than any other type of lung cancer.…”
Section: Introductionmentioning
confidence: 99%